GaN power amplifier for satellite communications - Gomes, Jorge Miguel Abrantes de Almeida (2014)
The satellite communications have become a valid alternative to conventional communications, through fiber or copper, in situations of catastrophe or even as complement to improve the quality of the services provided at a worldwide scale. Recently, radio frequency engineers have worked towards a reliable solution to replace the travelling wave tube amplifiers on board of the satellite communications. Despite the travelling wave tube amplifiers reveal a good performance, its weight, size and cost are a serious technical problem to the main satellite manufacturers. However, this scenario tends to change due to the exploitation of the Gallium Nitride technology in high power, efficiency and frequency applications. The objective of this work involves an implementation of two power amplifiers in class B, resorting to a Gallium Nitride transistors and using different types of planar transmission lines, for a 5.8GHz frequency which is often used in uplink transmissions for C-band or even in recent applications of wireless power transmission. The best results were obtained for the microstrip lines power amplifier, achieving 34.1dBm of output power, 62.35% of drain efficiency at saturation and a small-gain of 17dB.